2012
DOI: 10.1007/bf03262298
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Time Limit

Abstract: The ability to predict performance is of great interest for athletes and coaches. It is helpful for the selection of athletes to a team, the prescription of individualized training and the determination of the optimal pacing strategy. However, it is often difficult to judge the time to exhaustion without maximal exercise testing, which is often difficult to schedule during a competitive season. Consequently, the purpose of this review is to present a recent tool based on subjective prediction of time to exhaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In trail running, self-pacing has a major influence on performance (Millet, 2011a). It is well known that self-pacing exercise can be regulated from a complex protective system, including both somatosensory feedback and anticipatory mechanisms that maintain homeostasis and prevent major physiological disturbance (Coquart et al, 2012;Noakes, 2012) or motivational intensity changes (Marcora, 2008). Recently, Kerhervé et al (2015) observed that, during a 106-km mountain trail competition with a total elevation gain and loss of 5870 m, the trailers combined positive pacing strategies (speed decreased from the start until 70% -90% of the total event duration) with an increase of velocity in the last 10% of the event, and an increase in rating of perceived exertion (RPE) in the last 30% of the competition.…”
Section: Introductionmentioning
confidence: 99%
“…In trail running, self-pacing has a major influence on performance (Millet, 2011a). It is well known that self-pacing exercise can be regulated from a complex protective system, including both somatosensory feedback and anticipatory mechanisms that maintain homeostasis and prevent major physiological disturbance (Coquart et al, 2012;Noakes, 2012) or motivational intensity changes (Marcora, 2008). Recently, Kerhervé et al (2015) observed that, during a 106-km mountain trail competition with a total elevation gain and loss of 5870 m, the trailers combined positive pacing strategies (speed decreased from the start until 70% -90% of the total event duration) with an increase of velocity in the last 10% of the event, and an increase in rating of perceived exertion (RPE) in the last 30% of the competition.…”
Section: Introductionmentioning
confidence: 99%